Computer-Based System For Temperature Measurement Calibration Of Type-K Thermocouple - Najidah, Hambali; Shahrizal, Saat; Ahmad Nor Kasruddin, Nasir; Mohd Ashraf, Ahmad (2010)
Using the temperature calibration instrument, the purpose of this paper is to design the uncertainty calculation system. The test was conducted using Type-K thermocouple temperature sensor and repeated for three times. The data acquisition (DAQ) card is used to interface the temperature instrument and the computer. In order to determine the uncertainty of the temperature measurement, graphical user interface (GUI) software has been developed in Visual Basic(VB) programming language. The developed software shows that the uncertainty of the Type-K thermocouple temperature measurement can be calculated by interfacing the instrument to the computer through DAQ card. The study focuses on manual temperature measurement and concentrates only on Type-K thermocouple temperature measurement. The results provide the confidence limits of five-point calibration that could improve the teaching techniques using computerbased system of the temperature measurement.